2014
DOI: 10.1152/ajpgi.00005.2014
|View full text |Cite
|
Sign up to set email alerts
|

Pantoprazole decreases gastroesophageal muscle tone in newborn rats via rho-kinase inhibition

Abstract: Proton pump inhibitors reduce gastric acid secretion and are commonly utilized in the management of gastroesophageal reflux disease across all ages. Yet a decrease in lower esophageal sphincter tone has been reported in vitro in rats through an unknown mechanism; however, their effect on the gastroesophageal muscle tone early in life was never studied. Hypothesizing that proton pump inhibitors also reduce gastroesophageal muscle contraction in newborn and juvenile rats, we evaluated the in vitro effect of pant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In adult rat (36) and human (39) lower esophageal sphincters, ROCK inhibitors abolish both spontaneous basal and nerveevoked contractions. Recently, we reported a similar response to ROCK-2 inhibition in the newborn rat lower esophageal sphincter (48). In the present study, we documented a direct relationship between pyloric tissue ROCK-2 expression/activity and the magnitude of agonist-induced muscle contraction in newborn mice.…”
Section: Discussionsupporting
confidence: 83%
“…In adult rat (36) and human (39) lower esophageal sphincters, ROCK inhibitors abolish both spontaneous basal and nerveevoked contractions. Recently, we reported a similar response to ROCK-2 inhibition in the newborn rat lower esophageal sphincter (48). In the present study, we documented a direct relationship between pyloric tissue ROCK-2 expression/activity and the magnitude of agonist-induced muscle contraction in newborn mice.…”
Section: Discussionsupporting
confidence: 83%
“…The proposed mechanisms for these findings is thought to be the bacterial overgrowth related with the increased gastric pH, and the more frequent occurrence of bacterial aspiration. Adjunctive factors may be a potential decreased muscle tone due to PPIs and an influence on the function of neutrophil and natural-killer cells, which can cause a less efficient clearance of bacteria (Welsh et al, 2014;Gulmez et al, 2007). Taken together these preclinical data suggest that an overuse of PPIs during RT has the potential of increasing the risk of complications.…”
Section: Potential Drawbacks Of Ppis During Radiotherapymentioning
confidence: 96%
“…Interestingly, the proton pump inhibitor pantoprazole inhibited MYPT1 T853 phosphorylation evoked by CCh in gastric and LES tissue, suggesting that it may also be a ROCK inhibitor, although it had no effect on constitutive MYPT1 or CPI-17 phosphorylation. 114 It has been reported that PDBu-evoked contraction of cells isolated from human IAS smooth muscles are reduced by a ROCK inhibitor, but not by a PKC inhibitor, although PKC was activated, although another study reported that PDBu relaxes opossum IAS smooth muscles and cells isolated from opossum IAS smooth muscles. 97,115 Several of the studies previously mentioned examining CPI-17 and MYPT1 phosphorylation in response to contractile agonists show variable, but significant levels of constitutive CPI-17 and MYPT1 phosphorylation in the un-stimulated control tissues.…”
Section: Cpi-17 and Mypt1 Are Constitutively Phosphorylated In Gastromentioning
confidence: 98%